PEMBATALAN AKTA HIBAH (Studi Kasus Putusan Mahkamah Agung Nomor: 233/K/AG/2007) - , EKA TENRIABENG PRIHASYANTI HASAN, Prof. Dr. Abdul Ghofur Anshori, S.H.,M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
-